2016
DOI: 10.1002/1873-3468.12229
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐146a represses LRP2 translation and leads to cell apoptosis in Alzheimer's disease

Abstract: MicroRNA regulation of transcript expression has been reported in patients with Alzheimer's disease (AD). Here, we investigate the role of microRNA‐146a (miRNA‐146a), a brain‐enriched miRNA, which is upregulated in AD patients. Through analysis of predicted targets of miRNA‐146a, low‐density lipoprotein receptor‐related protein‐2 (Lrp2), a member of the LDLR family that is known to play a protective role in AD, was identified. Overexpression of miRNA‐146a in SH‐SY5Y cells significantly decreased Lrp2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…The reduced levels of TNF-RI, TNF-RII, and CCL2 may reflect differential expression by different cells in the demyelinating corpus callosum, and this can influence the ultimate protective versus detrimental effect; the observed protection from CPZ-induced demyelination is a combinatory effect of miR-146a deficiency in all cell types, and we cannot exclude the possibility that lack of miR-146a in particular cell types could be harmful. We hypothesize that pro-apoptotic properties of miR-146a ( 23 , 24 , 32 , 64 ) may also contribute to decreased demyelination, increased number of myelinating oligodendrocytes and reduced axonal loss during the demyelination phase induced by CPZ in KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced levels of TNF-RI, TNF-RII, and CCL2 may reflect differential expression by different cells in the demyelinating corpus callosum, and this can influence the ultimate protective versus detrimental effect; the observed protection from CPZ-induced demyelination is a combinatory effect of miR-146a deficiency in all cell types, and we cannot exclude the possibility that lack of miR-146a in particular cell types could be harmful. We hypothesize that pro-apoptotic properties of miR-146a ( 23 , 24 , 32 , 64 ) may also contribute to decreased demyelination, increased number of myelinating oligodendrocytes and reduced axonal loss during the demyelination phase induced by CPZ in KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a is involved in a negative feedback loop: it is induced by NF-kB, but also inhibits the activation of NF-κB ( 22 ). miR-146a is involved in cell death and survival; in glioma cells: overexpression of miR-146a suppressed cell survival, proliferation, and migration, whereas inhibition resulted in improved migration potential ( 23 , 24 ). miR-146a amplified the effect of a G-actin-sequestering peptide to promote OPC differentiation in vitro , and its overexpression in neural progenitor cells increased their differentiation into OPCs ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors affecting megalin expression cannot be excluded, including the possible effects of other miRNAs not examined in the present study. MiR-146a was previously shown to target megalin in brain to increase cell apoptosis in Alzheimer’s disease [ 41 ]. Differences in cell signaling pathways may account for this apparent discrepancy between brain and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation of KRAS and YY1 knockdown suggest the potential regulation between YY1 and miR-146a. Moreover, miR-146a induced cell apoptosis in PCa cells by activating cleaved caspase-3 (15). Collectively, these results indicated that YY1 depletion induced cell apoptosis of PCa at least in a miR-146a-assisted manner.…”
Section: Resultsmentioning
confidence: 99%